History of life [videorecording] : the evolution of mankind. (San Francisco, CA : Cerebullum Corp., 2014)
Life appeared on our planet many million of years ago. In this program, explore mankind's unwritten history and the theory of our evolution. Topics include: Characteristics of Prehistoric Man, Neanderthal, Cro-Magnon Men, Homo Sapiens, and Primates: their origins, characteristics, skulls and evolution.
Keywords: Evolution (Biology); Human evolution; Man -- origin